1997
DOI: 10.1016/s1078-5884(97)80179-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term prognosis for patients with chronic leg ulcers: a prospective cohort study

Abstract: Only patients with non-venous ulcers have a higher mortality than expected. The long-term healing prognosis for leg ulcer patients is poor and worst for patients with venous ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
1
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 25 publications
6
81
1
3
Order By: Relevance
“…3 Nelzen and colleagues in Sweden followed 382 patients who had open leg and/or foot ulcers in 1988 (206 with predominantly venous aetiology) for 5 years to determine healing and recurrence outcomes. 11 At follow-up, 58% of all patients had healed ulcers, 38% had open ulcers and 4% had undergone amputation. Looking at patients with ulceration due to venous incompetence (n = 135 at 54 months), only 44% had healed their original ulcer without subsequent recurrence compared with 59% of patients with arterial ulcers and 59% of people with diabetes.…”
Section: Long-term Outcomesmentioning
confidence: 96%
“…3 Nelzen and colleagues in Sweden followed 382 patients who had open leg and/or foot ulcers in 1988 (206 with predominantly venous aetiology) for 5 years to determine healing and recurrence outcomes. 11 At follow-up, 58% of all patients had healed ulcers, 38% had open ulcers and 4% had undergone amputation. Looking at patients with ulceration due to venous incompetence (n = 135 at 54 months), only 44% had healed their original ulcer without subsequent recurrence compared with 59% of patients with arterial ulcers and 59% of people with diabetes.…”
Section: Long-term Outcomesmentioning
confidence: 96%
“…Previous studies have assessed the effects of foot ulceration and osteomyelitis on morbidity and mortality in diabetic patients (28)(29)(30)(31); such studies suggest that patients with foot ulcers have reduced quality of life and increased morbidity and mortality when compared with patients without foot ulcers. Another study has shown that diabetic patients with foot ulcers have a lower survival rate when compared with nondiabetic patients with foot ulcers (32). The increased mortality associated with diabetic foot ulcers seems to result from the additional comorbidity-an interesting finding that requires further investigation.…”
Section: Oyibo and Associatesmentioning
confidence: 99%
“…1,2 The majority of care for these patients is delivered in the community, at a clinic location or at home, principally by teams of District Nurses (DN). 3 Evidence demonstrates that high compression, multilayer bandaging represents the 'gold standard' approach to the management of CVLU which, when correctly applied, improves healing times when compared to the absence of compression. 4,5 However, research suggests that much of the care for this patient group has an exclusive wound management focus which is of varying quality and little attention is paid to the impact that the ulceration poses on the individual.…”
Section: Introductionmentioning
confidence: 99%